2020
DOI: 10.1103/physrevapplied.13.064034
|View full text |Cite
|
Sign up to set email alerts
|

Optically Rewritable Memory in a Graphene–Ferroelectric-Photovoltaic Heterostructure

Abstract: Achieving optical operation of logic elements, especially those that involve two-dimensional (2D) layers, can begin the long-awaited era of optical computing. However, efficient optical modulation of the electronic properties of 2D materials, including the rewritable memory effect, is currently lacking. Here we report a fully optical control of the conductivity of graphene with write-erase operation yet under ultralow optical fluence. The competition between light-induced charge generation in a ferroelectric-p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 74 publications
(83 reference statements)
0
20
0
Order By: Relevance
“…Our findings therefore open a new avenue to photonic control of optical devices based on photo-ferroelectric crystals for all-optical modulators, memories and variety of optical logics, possibly extendable even to quantum effects [49] and 2D structures. [50]…”
Section: Discussionmentioning
confidence: 99%
“…Our findings therefore open a new avenue to photonic control of optical devices based on photo-ferroelectric crystals for all-optical modulators, memories and variety of optical logics, possibly extendable even to quantum effects [49] and 2D structures. [50]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the population of polar domains with different orientations and concomitant domain walls, in ferroelectric multidomain single crystals (BaTiO 3 , BTO), can be modulated by suitable coherent illumination 28 , 29 or ultrafast light pulses 30 . Polarization switching via light absorption at semiconducting electrodes (for instance, bidimensional MoS 2 ) 31 , 32 or subsidiary devices 33 , 34 has been reported, and it has been used to control device resistance by light and electric field in a three terminal ferroelectric field-effect device 35 , 36 . Exploitation of polarization reversal by light absorption within the ferroelectric remains rather unexplored 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the more technologically promising concepts involves optoelectronics employing domain walls, that is, light control of walls. [ 120–126 ] While initial demonstrations of wall manipulation with the light of various wavelengths have been brought forward, more detailed prototype device demonstrations remain to be shown. Closely related are high‐frequency electronic applications with domain walls in the Giga‐ and Tera‐Hertz range of the electromagnetic spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] Exploiting a coupling between the polarization and strain gradients or stress, [ 110,111 ] the localized mechanical stresses [ 76,112 ] can be used to effect polarization reversal and inject domain walls [ 46,113 ] or morphotropic phase boundaries, [ 114–117 ] although the approach may not be very practical for devices. Other alternative domain wall injection and control mechanisms that have been tried but are yet to be further developed include the imposition of macroscopic strain through bending, [ 118,119 ] optical impulses, [ 120–126 ] and magnetic and electric coupling. [ 127–132 ]…”
Section: State‐of‐the‐art Knowledgementioning
confidence: 99%